Tool geometry influence on the tensile load of copper–AA1100 joint using two stage refilled friction stir spot welding (TS-RFSSW) - Hikaru Trinita Salsabila; Ario Sunar Baskoro; Shafira Herdiyan Maritza Salsabila; Gandjar Kiswanto; Syarif Junaidi (BKS-TM Indonesia, 2025)
Two stage refilled friction stir spot welding (TS-RFSSW) is a method to eliminate keyholes formed in the friction stir spot welding (FSSW). This study aims to investigate the effect of tool geometry on the tensile shear loads of joints produced by TS-RFSSW. Copper and aluminum AA110 sheets with a thickness of 0.42 mm were joined using the TS-RFSSW process. The tools used in the first stage have taper and triangular pins. In the second stage, pinless tools with 5 mm and 6 mm diameters were used to close the keyhole. Other process parameters used included a dwell time of 4 seconds, a plunge depth of 600 µm, and a tool tilt angle of 0⁰. The TS-RFSSW process successfully produced improved joint surfaces with minimal keyholes, resulting in increased tensile shear loads. The tool with a triangular pin produced joints with higher tensile shear loads due to more intensive material flow. On the other hand, increasing the diameter of the pinless tool for the second stage reduced the tensile shear loads of the joints. The maximum tensile shear load achieved was 292.78 ± 34.72 N using a triangular pin tool for the first stage and a 5 mm pinless tool for the second stage.